Slippery Alkoxysilane Coatings for Antifouling Applications - Henry Apsey (ACS Applied Materials & Interfaces, 2023)
Herein, we report the wettability and antifouling behavior of a range of different siloxane coatings on plastic and glass substrates. The films investigated are prepared using trimethoxysilane precursors with different alkyl chain lengths (1–18 C atoms) in order to study how the nature of the hydrophobic group affects the different parameters used to characterize wettability (contact angles, sliding angles, and contact angle hysteresis). Atomic force microscopy analysis shows that the coatings possess low surface topography [root mean squared roughness (rms) < 50 nm] and are highly transparent as studied using UV–vis spectroscopy. The sliding properties of H2O, CH2I2, methanol, and ethylene glycol were observed to be strongly influenced by the chain length of the alkoxysilane precursor used. The coatings formed from the longer chain analogues show comparable water sliding angles to superhydrophobic surfaces. These coatings show similar performance to analogous alkoxysilane coating-bearing fluorinated groups, indicating that they could act as viable environmentally friendly alternatives to some of the fluorinated films that have been widely adopted. Furthermore, these surfaces are highly durable toward common forms of abrasion and are observed to show low adhesion toward synthetic feces, indicating that their utility extends further than repelling liquids alone. Consequently, these coatings could show promise for potential use in applications in the medical sector where fouling by biological mixtures leads to an unsustainable use of materials.